BUDAYA HUKUM DEBITOR DAN KREDITOR TERHADAP ASAS ITIKAD BAIK DALAM PELAKSANAAN HOMOLOGASI - Perdana, Mochamad Roland; Feisal, Azwar; Sari, Elsi Kartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze in depth the legal culture of debtors and creditors based on good faith in implementing the PKPU peace agreement. How the regulation of the principle of good faith in the peace agreement in the process of Suspension of Debt Payment Obligations (PKPU) based on UUK - PKPU and How the legal culture of business actors (debtors and creditors) influences the implementation of the principle of good faith in the implementation of the PKPU peace agreement is the main problem. This study is a normative study to examine in depth related to the legal culture regarding the implementation of good faith in the results of the agreement in PKPU. The statute approach and case study approach are the approaches used. The data used are primary data in the form of regulations related to UUK - PKPU and secondary data used are previous research and related information data. The results of this study indicate that the principle of good faith in the implementation of the peace agreement or homologation in PKPU is very important to ensure economic certainty and legal certainty for creditors and debtors. Cancellation of homologation is generally due to the debtor's default in fulfilling the terms of the homologation agreement, which can result in the homologation being revoked, automatically declaring the debtor bankrupt. Keywords: Legal Culture; Homologation; Good Faith